(untitled) (Sebha University Conference Proceedings, 2025)
In this research, the underwater optical wireless systems with the OPTISYSTEM system were identified, and what distinguishes it as a system in comparison with other underwater communication methods, where the elements affecting the spread of the light beam within the water channel were studied, and the necessary optical receivers and transmitters for that were identified, and the A transmission and reception system using a square signal from a pulse generator at different frequencies by simulating the system using OPTISYSTEM, by simulating a 1-meter long water channel, where two pairs of transmitters and receivers were developed with a speed of up to 100 Mbps, based on low-cost TO56 packages. , 520 nm LDS laser diodes, and 100 Mbps UWOCS two-way wireless optical communications system display modules. The effects of six types of seawater on the performance of the proposed communications system were qualitatively analyzed, which include pure seawater, deep seawater, coastal seawater, turbid seawater, and turbid seawater. The simulation results showed that the system relies on X-ray technology. Infrared or laser sends optical signals through water, allowing large amounts of data to be transmitted quickly and safely, as the error rate across the environment has reached 2%. Also, the higher the Q value, the better the SNR value; thus, the possibility of errors decreases. In the transmitted and received bits